Comprehensive quantification of sesame allergens in processed food using liquid chromatography-tandem mass spectrometry. (January 2020) - Ma, Xiuli; Li, Hong; Zhang, Jiukai; Huang, Wensheng; Han, Jianxun; Ge, Yiqiang; Sun, Jinlyu; Chen, Ying
Abstract: Sesame ( Sesamum indicum ) is a well-recognized food allergen, and sesame-related allergies have been increasingly reported worldwide. Patients with sesame allergy are specifically allergic to different sesame proteins (Ses i 1–7). Because of the increasing burden associated with allergies to sesame, there is an urgent need to develop sensitive and quantitative analytical methods capable of detecting sesame allergen contaminants. Targeted proteomic approach employing liquid chromatography/tandem mass spectrometry (LC-MS/MS) has emerged as a promising technique that offers increased specificity and reproducibility compared to antibody and DNA-based technologies. In this study, we developed a qualitative and absolute quantification method based on the LC-MS/MS-multiple reaction monitoring (MRM) system utilizing stable isotope-labeled internal standard (SIIS) peptides. We optimized extraction and trypsin digestion conditions and selected signature and absolute quantification (AQUA) peptides for seven sesame allergen proteins respectively. This quantitative method produced a linear relationship (R 2  > 0.99) in a wide concentration range (0.4–2000 fmol/μL), and the overall coefficient of variation was <5% in multiple tests. Limits of detection (LOD) and Limits of quantification (LOQ) for the seven sesame allergens AQUA peptides were determined to range from 0.1 to 140.0 fmol/μL and 0.4–400 fmol/μL respectively. The results showed that the accuracy of 20, 50, 100 ppm incurred protein Ses i 2 were 90%, 92%, 94% in non-processed material and 92%, 95%, 102% in processed material respectively. Overall, this method allowed for rapid and simultaneous absolute quantification of seven sesame allergens. The newly developed LC-MS/MS assay will likely increase the safety of sesame processed foods and add diagnostic value to the sesame allergy testing. Highlights: Targeted proteomic approach employing LC-MS/MS were used in this method. Signature and AQUA peptides for seven sesame allergens were selected respectively. The qualitative and quantitative method utilized LC-MS/MS-MRM and SIIS peptides. We optimized extraction, trypsin digestion and LC-MS/MS-MRM analysis conditions. Absolutely quantify seven sesame allergens rapidly and simultaneously in products.